Consider the sequence of steps to solve the equation: 2(x – 4) + 6x = 9x – 10 Given = 2(x – 4) + 6x = 9x – 10 Step 1 = 2x – 8 +

Question

Consider the sequence of steps to solve the equation: 2(x – 4) + 6x = 9x – 10
Given = 2(x – 4) + 6x = 9x – 10
Step 1 = 2x – 8 + 6x = 9x – 10
Step 2 = 2x + 6x – 8 = 9x – 10
Step 3 8x – 8 = 9x – 10
Step 4 = 8x – 8x – 8 = 9x – 8x – 10
Step 5 = 0 – 8 = x – 10
Step 6 = -8 = x – 10
Step 7 = -8 + 10 = x – 10 + 10
Step 8 = 2 = x + 0
Step 9 = 2 = x
Which step in solving this equation is justified by the Distributive Property?

in progress 0
Allison 4 weeks 2021-09-16T18:51:35+00:00 1 Answer 0

Answers ( )

    0
    2021-09-16T18:53:03+00:00

    step 1 because the 2 is multiplied by the (x-4)

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )